Newborn screening and the recommended uniform screening panel: Optimal submissions and suggested improvements based on an advocacy organization's decade‐long experience. Issue 2 (22nd September 2022) - Ellinwood, N. Matthew
Abstract: The National MPS Society, Inc., founded in 1974, is a rare disease advocacy non‐profit with a tripartite mission addressing the needs of the mucopolysaccharidosis and mucolipidosis communities through advocacy, research, and family and patient support. The Recommended Uniform Screening Panel (RUSP) of conditions for newborn screening (NBS), legislatively mandated in 2008, was implemented in 2010 by the Secretary of Health and Human Services (HSS), through the adoption of 29 core conditions. Since its inception the RUSP has grown to 35 core conditions. Each addition followed a defined nomination process that has itself undergone further definition over time. Since the adoption of the RUSP, the Society has nominated two conditions that have been approved by the Advisory Committee on Heritable Disorders in Children and Newborns (ACHDNC) and forwarded to the Secretary of HSS for inclusion on the RUSP. This history places the Society in a position to reflect on the process of successfully nominating conditions. Additionally, the Society is well placed by this experience to provide observations on the RUSP process. We will highlight best practices for pending and future nominations and reflect on potential improvements to the process and infrastructure of NBS, the RUSP, and the ACHDNC.